A review on self-healing polymers for soft robotics. (July 2021) - Terryn, Seppe; Langenbach, Jakob; Roels, Ellen; Brancart, Joost; Bakkali-Hassani, Camille; Poutrel, Quentin-Arthur; Georgopoulou, Antonia; George Thuruthel, Thomas; Safaei, Ali; Ferrentino, Pasquale; Sebastian, Tutu; Norvez, Sophie; et al.
Graphical abstract: Abstract: The intrinsic compliance of soft robots provides safety, a natural adaptation to its environment, allows to absorb shocks, and protects them against mechanical impacts. However, a literature study shows that the soft polymers used for their construction are susceptible to various types of damage, including fatigue, overloads, interfacial debonding, and cuts, tears and perforations by sharp objects. An economic and ecological solution is to construct future soft robotic systems out of self-healing polymers, incorporating the ability to heal damage. This review paper proposes criteria to evaluate the potential of a self-healing polymer to be used in soft robotic applications. Based on these soft robotics requirements and on defined performance parameters of the materials, linked to the mechanical and healing properties, the different types of self-healing polymers already available in literature are critically assessed and compared. In addition to a description of the state of the art on self-healing soft robotics, the paper discusses the driving forces and limitations to spur the interdisciplinary combination between self-healing polymer science and soft robotics.